Protective effect of Phyllanthus acidus (L) skeel fruits on attenuation of bleomycin-induced pulmonary fibrosis - Vallala Venkata Rajesham, Mitta Raghavendra, Pinjari Roshan Ali, Gaddam Supriya Reddy, Tadikonda Rama Rao (Journal of Applied Pharmaceutical Science, 2024)
Pulmonary fibrosis (PF) is a persistent and often lethal condition marked by initial alveolitis that advances to interstitial fibrosis. The pathological hallmark of PF is the presence of usual interstitial pneumonia on a biopsy. The aim of the present study was to study the protective effect of Phyllanthus acidus (L.) Skeels fruit against bleomycin-induced PF. The phytochemical analysis of the ethanolic extract showed alkaloids, saponins, phenols, flavonoids, tannins, and terpenoids as major metabolites. Bleomycin prompts an elevated production of reactive oxygen species, initiating an inflammatory response that may lead to pulmonary toxicity, activation of fibroblasts, and the subsequent onset of fibrosis. In this study, bleomycin was administered intratracheally at a dose of 4 mg/kg b. wt. the ethanolic extract at 100, 200, and 400 mg/kg body weight doses were used for screening protective effect against bleomycin-IPF. N-acetyl cysteine was used as a standard drug Tissue oxidant stress markers MDA, SOD, CAT, and GPx, was evaluated in lung tissue homogenate, and cell counts in the bronchoalveolar lavage fluid. The decreased MDA and increased SOD, CAT, and GPx levels were observed in treated groups after bleomycin administration. The increased cell counts were reduced to normal in PAE groups. In conclusion, Phyllanthus acidus (L.) Skeel fruits were useful for PF treatment.
Keywords: Phyllanthus acidus (L) skeel, pulmonary fibrosis, bleomycin, interstitial pneumonia